2017
DOI: 10.1364/josaa.34.001411
|View full text |Cite|
|
Sign up to set email alerts
|

Centralized inverse-Fano distribution for controlling conversion gain measurement accuracy of detector elements

Abstract: Statistical theory is applied to derive the centralized inverse-Fano distribution as a model for the probability distribution of the photon transfer conversion gain measurement for detector elements. This distribution is confirmed by experiment, thus supporting the theory and enhancing the credibility of the statistical model used. Analysis of the statistical distance between the derived functions and computationally fast approximate forms is carried out to determine the conditions when such approximations are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 3 publications
2
12
0
Order By: Relevance
“…where γ(a, x) ≡ x 0 t a−1 e −t dt is the lower incomplete gamma function. The same result can be obtained [4] by integrating the joint density…”
Section: Generalized Hypergeometric Functionsupporting
confidence: 55%
See 2 more Smart Citations
“…where γ(a, x) ≡ x 0 t a−1 e −t dt is the lower incomplete gamma function. The same result can be obtained [4] by integrating the joint density…”
Section: Generalized Hypergeometric Functionsupporting
confidence: 55%
“…This important form of f (x), which can also be found in [4], is not only much more economic and comprehensible as (2.2) or mentioned, more "messy" eq. ( 5) in [3], but it contains Tricomi's function (A5), one of the most commonly used hypergeometric functions with a wide variety of applications 2 .…”
Section: Remark 1 Special Functionsmentioning
confidence: 61%
See 1 more Smart Citation
“…For sensors that cannot achieve a shot noise limited response one cannot ignore the noise produced by the pixel in the absence of illumination. As such, Hendrickson studied the estimator [13]…”
Section: Previous Workmentioning
confidence: 99%
“…While convenient, the lack of distributional assumptions on the estimator (1.2) is not all that important. Indeed, many authors have shown that most image sensors produce noise that is accurately modeled as normal [16,3,13]. Even in the case where the pixel noise exhibits departures from normality, pt typically requires large samples sizes such that the distributions of the sample statistics ( X, Ȳ , X, Ŷ ) show excellent agreement with what is predicted by a normal model.…”
Section: Introductionmentioning
confidence: 99%